2019
DOI: 10.1002/path.5342
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor FOXM1 regulates the balance between proliferation and aberrant differentiation in head and neck squamous cell carcinoma

Abstract: Sustained expression of FOXM1 is a hallmark of nearly all human cancers including squamous cell carcinomas of the head and neck (HNSCC). HNSCCs partially preserve the epithelial differentiation program, which recapitulates fetal and adult traits of the tissue of tumor origin but is deregulated by genetic alterations and tumor-supporting pathways. Using shRNA-mediated knockdown, we demonstrate a minimal impact of FOXM1 on proliferation and migration of HNSCC cell lines under standard cell culture conditions. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Moreover, several pieces of evidence have reported that upregulation of DNA replication and cell-cycle pathways genes in HNSCC [43][44][45]. Others have proposed that overexpression of the RRM2, GTSE1 and EXO1 genes in HNSCC have active roles in tumor progression and inhibition of the apoptosis pathway [46][47][48][49]. Some researchers have suggested that the HPRT1 gene, as a crucial component of the purine salvage pathway, plays a role in mediating the proliferation, autophagy and apoptosis-related processes in cancer cells [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several pieces of evidence have reported that upregulation of DNA replication and cell-cycle pathways genes in HNSCC [43][44][45]. Others have proposed that overexpression of the RRM2, GTSE1 and EXO1 genes in HNSCC have active roles in tumor progression and inhibition of the apoptosis pathway [46][47][48][49]. Some researchers have suggested that the HPRT1 gene, as a crucial component of the purine salvage pathway, plays a role in mediating the proliferation, autophagy and apoptosis-related processes in cancer cells [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Roh et al [ 52 ] demonstrated that FOXM1 contributes to cell cycle promoting function in HNSCC cell lines and is responsible for cell proliferation and metastasis of HNSCC cells. Also, shRNA-mediated FOXM1 knockdown led to the diminished proliferation and reduced cell migration in three-dimensional culture and xenograft tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to further expand the understanding of the relationship between differentiation and RGR, we assessed the aberrant differentiation of SCC by involucrin staining. Involucrin, a marker of squamous differentiation, is expressed mainly by irreversibly differentiated keratinocytes in the stratum corneum and has been found to be markedly associated with aberrant differentiation in SCC ( 29 , 30 ). Comparison of RGR expression among different regions with different degrees of differentiation in the same sample showed that the degree of differentiation was inversely correlated with RGR expression, but positively correlated with involucrin expression.…”
Section: Discussionmentioning
confidence: 99%